Macrozoobenthos Diversity as an Indicator of the Water Quality of the Salusu River in Ogomatanang Village, Central Sulawesi and Its Use as a Learning Media - Zainal*, Syech; Agni, Raya; Mahardika, Dayu; Supriyadi, Supriyadi; Andriyanto, Andriyanto; Isnawati, Isnawati (Jurnal Pendidikan Sains Indonesia, 2024)
The diversity of macrozoobenthos plays an important role as an indicator of water quality. The purpose of this study was to describe the level of macrozoobenthos diversity in the waters of the Salusu River, Ogomatanang Village, Central Sulawesi as an indicator of pollution levels and to produce suitable learning media. The type of research is descriptive. The sampling technique used systematic random and used a subber net using a zig-zag transect line and analyzed the diversity index value. The results of the study found 9 species, divided into 8 families including Baetis sp., Alloperla sp., Parathelphusa convexa, Heptagenia solitaria, Orthetrum sabina, Nemoura sp., Tylomelania arabica, Tylomelania sp., Planaria sp. The diversity index (H') was consecutively at station III (upstream) which was 2.14 with a light level of pollution, the H 'index at station II (ecotone) was 1.91 and the H 'index at station I (downstream) was 1.28 with a moderate level of pollution. The research results obtained were used as validated learning media by a team of content experts by 80%, design 78.6%, media 80%, large group student group trials 85.5% and small group 89.0%. Learning media is very feasible to use with a result of 82.62%.